P PEMBAGIAN WARIS ISLAM - Fareha, Faathin (At-Ta'aruf : Jurnal Hukum Keluarga Islam, 2025)
Inheritance distribution presents a critical issue in both legal and social aspects, particularly when examined through the lens of gender equality. This research invetigates the application of the double movement theory within the inheritance distribution process, highlighting the dynamic interaction between formal legal norms and social realities. Specifically, this study explores how sociological aspects influence judisial decisions concerning gender equality in inheritance. The findings underscore the imperative for legal reforms that are more responcive to prevailing social realities. This necessitates a profound understanding of the interplay between legal norms and sociological contexts. This article recommends that policymakers formulate policies that are more aligned with the principles of social justice. Such reforms aim to foster a comprehensive understanding of inheritance distribution in Islamic law, considering both sociological aspects and the double movement theory. This is achieved through a normative-empirical approach, integrating literature review with in-depth analysis of judicial decisions. Keywords: inheritance distribution, judicial decisions, double movement theory.